Development and performance analysis of electro textile antenna by using copper-covered yarn for GPS application / M.S.Amin Nordin … [et al.] - Abd Rahman, N.H.; Ali, M.T.; Ahmad Shah, A.A.Sharatol; Zaidi, N.I.; Ahmad, M.R. (Universiti Teknologi MARA, 2019)
Development and performance analysis of electro textile antenna by using copper-covered yarn for GPS application / M.S.Amin Nordin … The validation of the performance of electro-textile antenna, designed for on-body communication by using coppercovered yarn as a conductive fabric was presented in this paper. The antenna was designed by using a self-manufactured conductive fabric thus, the properties of the textile such as dielectric constant (εr), loss tangent (tan δ) and conductivity (σ) value shall be determined. The antenna was designed at 1.575 GHz based on the allocated spectrum for Global Positioning System (GPS) application. In this research, the performance of electro-textile antenna on customized copper-covered yarns material was designed and validated through electromagnetic simulation and fabrication. Good agreement between simulation and measurement was obtained, where both results give correct resonant frequency and good radiation pattern performance. The compositions of the customized copper-covered yarn as the conductive fabric were presented. The copper-covered yarn was formed by polyester threads (non-conductive) that were twisted with copper threads (conductive) with the ratio of 17.1% and 82.9% respectively. The results show that the resonant frequency, from the measured data of electro-textile antenna prototype has a return loss of -20.56 dB at 1.575GHz. Simulation and experimental results including radiation patterns in the Eplane and H-plane were presented and discussed. Moreover, the effect of bending on the electro-textile antenna have been simulated and measured to determine the degradation of the return loss, bandwidth and radiation pattern.